Pelatihan Budidaya Sayur Hidroponik di Kampung Yasa Mulya - Panga, Nurhaya Jahidin; Widijastuti, Rosmala; Sarijan, Abdullah; Ekowati, Nurhening Yuni; Ginting, Nina Maksimiliana (MALLOMO: Journal of Community Service, 2022)
Hydroponic vegetable cultivation has the potential to be developed in Merauke Regency, including in Yasa Mulya Village, Tanah Miring District, Merauke Regency, Papua. This training aims to increase public interest and knowledge about hydroponic vegetable cultivation. The target of this activity is the residents of Yasa Mulya Village. The training which was attended by 22 participants was carried out using lecture methods, demonstrations and direct practice of hydroponic wick systems by the trainees. From the implementation of this activity, it can be concluded that the residents of Yasa Mulya Village have a high interest in cultivating vegetables hydroponically, and the training activities that have been carried out can significantly increase public knowledge about hydroponics. Budidaya sayur secara hidroponik sangat potensial dikembangkan di Kabupaten Merauke, termasuk di Kampung Yasa Mulya, Distrik Tanah Miring, Kabupaten Merauke, Papua. Pelatihan ini bertujuan untuk meningkatkan minat dan pengetahuan masyarakat mengenai budidaya tanaman sayuran secara hidroponik. Sasaran kegiatan ini adalah warga Kampung Yasa Mulya. Pelatihan yang diikuti oleh 22 peserta ini dilakukan dengan metode ceramah, demonstrasi dan praktik langsung hidroponik sistem wick oleh peserta pelatihan. Dari pelaksanaan kegiatan ini dapat ditarik kesimpulan warga Kampung Yasa Mulya memiliki ketertarikan yang tinggi untuk melakukan budidaya tanaman sayuran secara hidroponik, dan kegiatan pelatihan yang telah dilakukan dapat meningkatkan pengetahuan masyarakat mengenai hidroponik secara signifikan.